Factors Related to Covid-19 Vaccine Administration - Nur Afni; Sriwahyudin Moonti; Riwasni (Universitas Muhammadiyah Palu, 2022)
The spread of covid around the world is very fast and widespread. As of October 27, 2021, the number of covid patients in the world is 245,892,119 cases. The efforts made by the government in reducing the spread of the Covid 19 virus are through vaccination. The purpose of this study is to determine the factors related to the administration of the Covid-19 Vaccine at the Biddokkes Polyclinic of the Central Sulawesi Regional Police. This type of research is analytical research with quantitative methods with correlative techniques through a Cross sectional design approach. The population in this study was people who visited the Biddokkes Polyclinic of the Central Sulawesi Regional Police at the time of the study, with the number of samples being 96 people. The analysis used is univariate and bivariate analysis. There is no relationship between knowledge and vaccine administration at the Biddokkes Polyclinic of the Central Sulawesi Regional Police with a p value of 0.153. There is a relationship between attitudes and vaccine administration at the Biddokkes Polyclinic of the Central Sulawesi Regional Police with a p value of 0.040 and there is no relationship between the action and the administration of vaccines at the Biddokkes Polyclinic of the Central Sulawesi Regional Police with a p value of 0.667. It is hoped that health workers will maintain and can further improve good communication with the community in order to achieve smoothness and success in the vaccination program launched by the government and can realize herd Immunity in Indonesia.